2018
DOI: 10.1186/s12953-018-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

In-depth proteomic analyses of Haliotis laevigata (greenlip abalone) nacre and prismatic organic shell matrix

Abstract: BackgroundThe shells of various Haliotis species have served as models of invertebrate biomineralization and physical shell properties for more than 20 years. A focus of this research has been the nacreous inner layer of the shell with its conspicuous arrangement of aragonite platelets, resembling in cross-section a brick-and-mortar wall. In comparison, the outer, less stable, calcitic prismatic layer has received much less attention. One of the first molluscan shell proteins to be characterized at the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 139 publications
2
20
1
Order By: Relevance
“…The spatial distributions of AMELX, AMBN, ENAM, MMP20, and KLK4 (Figures 1D, 4) agree very well with published data on abundance patterns during specific stages of enamel formation (see Moradian-Oldak, 2012; Bartlett, 2013; Lacruz et al, 2017 and references therein). Our findings are consistent with the number and identifications of proteins of recently published proteomics analyses of pooled human and rodent enamel (Chen et al, 1995; Hubbard and Kon, 2002; Jagr et al, 2012, 2014; Eckhardt et al, 2014; Charone et al, 2016; Pandya et al, 2017; De Lima Leite et al, 2018; Mann et al, 2018; Zhang et al, 2018). For instance, we mapped 19 of the 24 proteins recently reported in enamel onto enamel formation stages (Pandya et al, 2017), and localized close homologs for the remaining five proteins (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…The spatial distributions of AMELX, AMBN, ENAM, MMP20, and KLK4 (Figures 1D, 4) agree very well with published data on abundance patterns during specific stages of enamel formation (see Moradian-Oldak, 2012; Bartlett, 2013; Lacruz et al, 2017 and references therein). Our findings are consistent with the number and identifications of proteins of recently published proteomics analyses of pooled human and rodent enamel (Chen et al, 1995; Hubbard and Kon, 2002; Jagr et al, 2012, 2014; Eckhardt et al, 2014; Charone et al, 2016; Pandya et al, 2017; De Lima Leite et al, 2018; Mann et al, 2018; Zhang et al, 2018). For instance, we mapped 19 of the 24 proteins recently reported in enamel onto enamel formation stages (Pandya et al, 2017), and localized close homologs for the remaining five proteins (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…BLASTp-based comparisons of the L. stagnalis shell proteome were performed against a variety of calcifying proteomes reported in a wide phylogenetic range of metazoans as described in [ 14 ]. These included 42 proteins from the oyster Pinctada maxima reported in [ 47 ]; 78 proteins from the oyster Pinctada margaritifera reported in [ 47 ]; 94 proteins from the abalone Haliotis asinina reported in [ 17 ] and [ 16 ]; 80 proteins from the abalone H. laevigata reported in [ 48 ]; 63 proteins from the limpet Lottia gigantea reported in [ 49 ]; 53 proteins from the oyster Crassostrea gigas reported in [ 50 ]; 71 proteins from the mussel Mya truncata reported in [ 51 ]; 59 proteins from the grove snail Cepaea nemoralis reported in [ 14 ]; 44 proteins from the oyster Pinctada fucata reported in [ 52 ]; 53 proteins from the mussel Mytilus coruscus reported in [ 53 ]; 66 proteins from the brachiopod Magellania venosa reported in [ 54 ]; 139 proteins from the sea urchin Strongylocentrotus purpuratus reported in [ 55 ]; and 37 proteins from the coral Acropora millepora reported in [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tyrosinases catalyze the oxidation of both monophenols and o-diphenols into reactive o-quinones (Garcia-Borron and Solano, 2002). Data from shell proteomics showed that tyrosinases were incorporated into the shell matrices in the prismatic layer (Nagai et al, 2007;Liao et al, 2015;Mann et al, 2018), nacre layer (Mann et al, 2018), and even the whole shell (Zhang et al, 2012;Du et al, 2017) of molluscan species. Recent research showed that tyrosinases participated in periostracum sclerotization and the cross-linking and maturation of shell matrix proteins by catalyzing the quinoprotein oxidation (Zhang et al, 2012;Aguilera et al, 2014;Du et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that tyrosinases are strongly expressed in the pallial and edge of the mantle, which are the main biomineralization tissues of Mollusca (Zhang et al, 2006a;Nagai et al, 2007;Yu et al, 2014;Huening et al, 2016;Yang et al, 2017), and tyrosinase proteins have also been detected in the proteome of the shell prismatic layer and/or nacreous layer (Marie et al, 2012;Liao et al, 2015;Mann et al, 2018). These results implied the crucial functions of tyrosinases in periostracum sclerotization and the cross-linking and maturation of shell matrix proteins (Zhang et al, 2012;Aguilera et al, 2014;Huening et al, 2016;Du et al, 2017).…”
Section: Introductionmentioning
confidence: 85%